The genome sequence of a snail-killing fly, Dichetophora obliterata (Fabricius, 1805) [version 1; peer review: 2 approved] - Olga Sivell; Duncan Sivell; Ryan Mitchell; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from a female specimen of Dichetophora obliterata (snail-killing fly; Arthropoda; Insecta; Diptera; Sciomyzidae). The genome sequence has a total length of 1,312.79 megabases. Most of the assembly (99.78%) is scaffolded into 6 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 21.36 kilobases. Gene annotation of this assembly on Ensembl identified 15,139 protein-coding genes.